Welcome to the Neighborhood: Assessing Localized Social Media Use and Pro-Community Attitudes in a Multi-National Survey - Marianne Aubin Le Quéré; Sanjay R. Kairam (Social Media + Society)
In the void left by struggling local media, localized social media systems have proliferated on the web as key avenues for the exchange of location-specific information. Yet, as local ecosystems shift, there is a need to understand the types of audiences localized social media spaces attract, and whether these spaces can foster healthy communities. This article presents the results of a multi-national, longitudinal user survey of participants ( N  = 2789) on the social media platform Reddit. We show, for the first time, that people who join localized social media spaces also report higher community attachment and political participation intent than users who join other social media spaces. We find evidence that these pro-community attitudes are stronger for longer-term members of localized social media and those who actively contribute through posts and comments. Surprisingly, we also identify that new residents to an area are more likely to belong to a localized social media forum than long-time residents. This article provides context for how the affordances of technology platforms influence the audiences, behaviors, and community impacts of localized social networks.